Is the Over-the-Head Technique an Alternative for Infant CPR Performed by a Single Rescuer? A Randomized Simulation Study with Lifeguards - Silvia Aranda-García; Silvia San Román-Mata; Martín Otero-Agra; Antonio Rodríguez-Núñez; María Fernández-Méndez; Rubén Navarro-Patón; Roberto Barcala-Furelos (MDPI AG, 2024)
(1) Objective: The objective was to evaluate the quality of cardiopulmonary resuscitation (CPR, chest compressions and ventilations) when performed by a lone first responder on an infant victim via the over-the-head technique (OTH) with bag-mask ventilation in comparison with the standard lateral technique (LAT) position. (2) Methods: A randomized simulation crossover study in a baby manikin was conducted. A total of 28 first responders performed each of the techniques in two separate CPR tests (15:2 chest compressions:ventilations ratio), each lasting 5 min with a 15 min resting period. Quality CPR parameters were assessed using an app connected to the manikin. Those variables were related to chest compressions (CC: depth, rate, and correct CC point) and ventilation (number of effective ventilations). Additional variables included perceptions of the ease of execution of CPR. (3) Results: The median global CPR quality (integrated CC + V) was 82% with OTH and 79% with LAT (p = 0.94), whilst the CC quality was 88% with OTH and 80% with LAT (p = 0.67), and ventilation quality was 85% with OTH and 85% with LAT (p = 0.98). Correct chest release was significantly better with OTH (OTH: 92% vs. LAT: 62%, p < 0.001). There were no statistically significant differences in the remaining variables. Ease of execution perceptions favored the use of LAT over OTH. (4) Conclusions: Chest compressions and ventilations can be performed with similar quality in an infant manikin by lifeguards both with the standard recommended position (LAT) and the alternative OTH. This option could give some advantages in terms of optimal chest release between compressions. Our results should encourage the assessment of OTH in some selected cases and situations as when a lone rescuer is present and/or there are physical conditions that could impede the lateral rescue position.